Malignant granular cell tumour at the interventricular septum. (7th April 2022) - Lou, Weng-Kin; Chou, Heng-Wen; Chen, Tom Wei-Wu; Hsu, Che-Yu; Chen, Jeng-Wei
Abstract: Granular cell tumours are usually benign with a 1–2% incidence of malignancy. They are less sensitive to radiotherapy and chemotherapy and are treated by surgical excision. We report a case of a malignant granular cell tumour located at the interventricular septum. Abstract : Granular cell tumour (GCT) was first described by a Russian pathologist, Abrikossoff, in 1926 [1].